1999
DOI: 10.1084/jem.189.8.1229
|View full text |Cite
|
Sign up to set email alerts
|

Signal Transducer and Activator of  Transcription (STAT)5 Activation by BCR/ABL Is Dependent on Intact Src Homology (SH)3 and SH2 Domains of BCR/ABL and Is Required for Leukemogenesis

Abstract: Signal transducer and activator of transcription (STAT)5 is constitutively activated in BCR/ ABL-expressing cells, but the mechanisms and functional consequences of such activation are unknown. We show here that BCR/ABL induces phosphorylation and activation of STAT5 by a mechanism that requires the BCR/ABL Src homology (SH)2 domain and the proline-rich binding site of the SH3 domain. Upon expression in 32Dcl3 growth factor–dependent myeloid precursor cells, STAT5 activation–deficient BCR/ABL SH3+SH2 domain mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
242
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 248 publications
(255 citation statements)
references
References 88 publications
10
242
0
Order By: Relevance
“…Constitutive STAT activation has been especially well characterized in leukemias, and a growing body of evidence in both acute and chronic leukemias suggests that derangements in the STAT signaling pathway may be critical to the development of cancer in hematopoietic cells (CatlettFalcone et al, 1999;Frank et al, 1997;GouilleuxGruart et al, 1996;Nieborowska-Skorska et al, 1999;Weber-Nordt et al, 1996;Zhang et al, 1996). The multitude of hematologic cancers which demonstrate abnormal STAT activation suggests that the STAT pathway may play an important role in the pathogenesis of malignancy and may serve as an attractive target of anti-cancer therapies.…”
Section: Stat Signaling Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Constitutive STAT activation has been especially well characterized in leukemias, and a growing body of evidence in both acute and chronic leukemias suggests that derangements in the STAT signaling pathway may be critical to the development of cancer in hematopoietic cells (CatlettFalcone et al, 1999;Frank et al, 1997;GouilleuxGruart et al, 1996;Nieborowska-Skorska et al, 1999;Weber-Nordt et al, 1996;Zhang et al, 1996). The multitude of hematologic cancers which demonstrate abnormal STAT activation suggests that the STAT pathway may play an important role in the pathogenesis of malignancy and may serve as an attractive target of anti-cancer therapies.…”
Section: Stat Signaling Pathwaymentioning
confidence: 99%
“…The physical interaction of Bcr/Abl and STAT5 was further delineated by Nieborowska-Skorska et al (1999) using retroviral expression of Bcr/Abl mutants in 32Dc13 cells. Speci®cally, single point and deletion mutations of the SH2 and SH3 domains were used to de®ne the necessity of these two domains for tyrosine phosphorylation and activation of STAT5 by Bcr/Abl.…”
Section: Chronic Myelogenous Leukemiamentioning
confidence: 99%
“…JAK/STATs are also implicated in the downstream of BCR-ABL protein, which activates the JAK/STAT pathway by its constitutive tyrosine kinase activity [3]. It has been shown that the BCR-ABL induces the STAT5 activation, which leads to leukemogenesis [4]. Loss of SOCS1 gene could play an important role in the regulation and progression of leukomogenesis in CML.…”
Section: Introductionmentioning
confidence: 99%
“…Jak-2 and IL-3/IL-5/GM-CSFRb was detected in the immunoprecipitates by Western blot assay with the speci®c antibodies (b and c, lower panels) Discussion BCR/ABL activates multiple signaling pathways leading to the transformation of hematopoietic cells (Raitano et al, 1997, Sattler andSalgia, 1997). These pathways are activated by several domains or amino acid residues of BCR/ABL such as SH1 (kinase domain), SH2, SH3, Y177, Y1294 or R1053 (Pendergast et al, 1993a,b;Afar et al, 1994;Goga et al, 1995;Cortez et al, 1995;Anderson et al, 1996;Skorski et al, 1997a;Salomoni et al, 1998;Nieborowska-Skorska et al, 1999), which are recognized as potential targets for the novel antitumor compounds. In this study we have shown that lack of activation of the BCR/ABLdependent signaling pathway(s) due to the mutation/ deletion of the particular BCR/ABL domain could be rescued by the alternative mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…This phenotype is associated with enhanced expression/activation of several e ectors (Raitano et al, 1997;Sattler and Salgia, 1997) such as Ras (Skorski et al, 1994;Sawyers et al, 1995), Rac (Skorski et al, 1998b), Raf-1 (Skorski et al, 1995a), PI-3k (Varticovski et al, 1991;Skorski et al, 1995cSkorski et al, , 1997a, Akt (Skorski et al, 1997a;Neshat et al, 2000), Bcl-2 (Sanchez-Garcia and Grutz, 1995), nuclear factor (NF)-kB (Reuther et al, 1998), CRKL (Senechal et al, 1996;Bhat et al, 1997), and STAT5 (Carlesso et al, 1996;Frank and Varticovski, 1996;Ilaria and VanEtten, 1996;Shuai et al, 1996;Chai et al, 1997;Nieborowska-Skorska et al, 1999;DeGroot et al, 1999;Sillaber et al, 2000;Horita et al, 2000). These proteins are stimulated by various functional domains/motifs of BCR/ABL (Pendergast et al, 1993a, b;Afar et al, 1994;Goga et al, 1995;Cortez et al, 1995;Anderson et al, 1996;Skorski et al, 1997a;Salomoni et al, 1998;Nieborowska-Skorska et al, 1999). Our previous studies demonstrated that signaling from SH2 or SH3+SH2 domain of BCR/ABL could be responsible for the induction of PI-3k/Akt (Skorski et al, 1997a) and STAT5 (NieborowskaSkorska et al, 1999), respectively.…”
Section: Introductionmentioning
confidence: 99%